Hydrothermally doping valve metal Nb into Titanate nanofibers structure for potentially engineering bone tissue - Tian, Yang; Cole, Parker; Xiao, Yiting; Akhter, Abdussamad; Collins, Trenton; Zhang, Lu; Huang, Yan; Tian, Z. Ryan (Nano and Medical Materials, 2024)
Recent research efforts in bone tissue engineering have been primarily directed towards manufacture-viable synthesis of biomaterials that can significantly enhance the biocompatibilities and osteogenic capabilities on the new biomaterials. This paper presents a straightforward, cost-effective, optimized, and well-controlled hydrothermal synthesis of Nb-doped potassium titanate nanofibers in high-purity. Characterization data revealed that the Nb-doping potassium titanate maintained the crystal structure, showing great promise for applications in bone tissue engineering.